Hodnocení finanční situace podniku a návrhy na její zlepšení - Faltusová, Eliška (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Předmětem bakalářské práce „Hodnocení finanční situace podniku a návrhy na její zlepšení“ je analýza současného stavu konkrétní společnosti a návrh na zlepšení její finanční situace. V teoretické části uvedu cíle mé práce, představím společnost a následně použité metody vedoucí ke zlepšení finanční situace ve společnosti. Ve druhé části provedu samotnou analýzu se zaměřením na její problematické části a popíši návrhy na zlepšení situace.

The subject of this bachelor thesis named „Evaluation of the financial situation of a company and proposals for its improvement“ is an analysis of current status of specific company and a suggestion for improvement of its financial situation. The goals of my thesis are listed in theoretical part, together with the introduction of the company and methods used to improve the financial situation of the company. In the second part I focus on analysis and its problematic parts and I also describe the suggestions for improvement of the situation.
Evaluation of the Financial Situation of the Company and Proposals to its Improvement
Keywords: finanční analýza; rozvaha; aktiva; pasiva; výkaz zisku a ztráty; náklady; výnosy; financial analysis; balance; assetes; liabilities; profit and loss statement; cosi; revenues